TEACHER STRATEGIES IN IMPLEMENTING HINDU LEARNING FOR EARLY CHILDHOOD - Lestiawati, I Made; Hartati, Sofia; Dhieni, Nurbiana (Sanata Dharma University Yogyakarta, 2023)
The purpose of this study is to describe teacher strategies in implementing Hindu nuanced learning, the lack of information related to the teacher in its application so that there needs to be an innovation created by the teacher to provide good practices for early childhood education through several learning strategies used by class teachers in one of PAUD Pratama Widya Pasraman in Tabanan district. The research method used is qualitative research with taxonomic data analysis techniques. The results showed several teacher strategies in implementing Hindu nuanced learning, divided into the first three stages, understanding Hindu nuanced learning. Second, planning learning, and Third, management in the learning process. The Hindu nuanced learning that is instilled is the concept of Tri Kaya Parisudha, Tri Pramana, Dwi Pramana, Eka Pramana, and Catur Guru.